Dampak Sosial dan Ekonomi Penggusuran Warung Ilegal di Bantaran Rel Kereta di Kawasan Stadion Maulana Yusuf Kota Serang Tahun 2025 - Rosidin, Angga (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to analyze the social and economic impacts of the policy to evict illegal stalls along the railroad tracks in the Maulana Yusuf Stadium area, Serang City, which was implemented in early 2025. This policy was adopted by PT. Kereta Api Indonesia (Persero) and the Serang City Government on the grounds of regulating state assets, ensuring train safety, and urban spatial planning. Using a qualitative approach and case study method, this research collected data through in-depth interviews with displaced vendors, observations at the post-eviction site, and analysis of relevant documentation. The results of the study indicate that the eviction had a significant economic impact on the vendors, including loss of primary income sources, increased debt, and loss of business assets. From a social perspective, the impacts felt include social displacement, loss of community networks among vendors, and psychological stress due to uncertainty about the future. Although the objective of regulation was achieved with the railway embankment area becoming cleaner and more orderly, this study found that the relocation solutions or alternative empowerment programs offered by the government have not effectively addressed the needs of the vendors. This study recommends the need for more humane and participatory urban planning policies that not only focus on the physical aspects of the city but also on the sustainability of its residents’ livelihoods.